2015
DOI: 10.5433/1679-0359.2015v36n2p1067
|View full text |Cite
|
Sign up to set email alerts
|

Propolis extract in the diet of crossbred (½ Angus vs. ½ Nellore) bulls finished in feedlot: animal performance, feed efficiency and carcass characteristics

Abstract: Current research studied the replacement of monensin by propolis on performance, feed efficiency and carcass characteristic of bulls finished in feedlot. The bulls, kept in feedlot for 70 days, were allocated in three diets: Control (CON), Monensin (MON) and Propolis (PRO). They were fed on corn silage, cracked corn, soybean meal, urea, limestone and mineral salt. Further, 250 mg monensin and 35 g propolis/bulls/day were included respectively in the MON and PRO diets. Animal performance and carcass characteris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 16 publications
1
4
0
1
Order By: Relevance
“…When the NDF content of a forage increases, the digestion rate decreases, and intake was reduced. Our results agreed with the findings of Valero et al (2015) ranged from 1.87 to 2.07%. In this study, it was found that the water consumption was gradually increased (P<0.05) by increasing NDF in diets.…”
Section: Feed Nutrient and Me Intakessupporting
confidence: 93%
“…When the NDF content of a forage increases, the digestion rate decreases, and intake was reduced. Our results agreed with the findings of Valero et al (2015) ranged from 1.87 to 2.07%. In this study, it was found that the water consumption was gradually increased (P<0.05) by increasing NDF in diets.…”
Section: Feed Nutrient and Me Intakessupporting
confidence: 93%
“…The test subjects have been different animal species, including poultry (chickens, laying hens, quails) [35][36][37][38][39][40][41][42][43][44][45][46][47][48], lambs [49,50], cattle [51], sheep [52], pigs [53], and fish: sea bass [54], rainbow trout [55][56][57], Nile tilapia [58][59][60], and carp [61] (Table 2). In general, propolis has a positive effect on the biochemical parameters, growth and productivity of the test animals, and is regarded as a possible alternative to antibiotics in animal feed.…”
Section: New Fields Of Propolis Applicationmentioning
confidence: 99%
“…However, the large-scale commercial use of propolis as a food preservative is not yet a reality, because it would require proper standardization. [35] Ross 308 Broiler Chick (heat stressed) 70% Ethanol extract Eastern Anatolia [36,37] Broiler chicks (male Ross 708) -Brazilian green type [38] Broiler chickens 70% Ethanol extract Poplar type, Iran [39] Broilers (Ross 308) 70% Ethanol extract Poplar type, China [40] Broiler chickens 50% Ethanol extract Adquirió en Maringá-PR, Brazil [41] Chickens Hubbard JV 80% Ethanol extract Slovak Republic [42] Chicken hybrid combination Ross 308 80% Ethanol extract Slovak Republic [43] Meat-type chicken Nanbu Kashiwa Propolis residue after alcohol extraction Iwate, Japan [44] Broiler chick Alcoholic extract Brazilian green type [45] Local quails Raw propolis Duhok, Iraq [46] Laying hens, heat stressed 70% Ethanol extract Eastern Anatolia [47] Hens' egg incubation -Central zone of Republic of Moldova [48] Ungulate domestic animals Lambs 70% Ethanol extract Brazilian green propolis [49] Lambs (Santa Inês x Dorper) 70% Ethanol extract Brazilian red propolis [50] Crossbred (½ Angus vs. ½ Nellore) bulls Ethanol extract Maringá PR, Brazil [51] Castrated male sheep 70% Ethanol extract Pernambuco State, Brazil. [52] Growing pigs 70% Ethanol extract Poplar propolis [53] Fish Juvenile European sea bass (Dicentrarchus labrax L.) at low temperature stress Water extract Dalmatia region, middle Croatia [54] Rainbow trout (Oncorhynchus mykiss) 95% Ethanol extract Kunming, China [55] Rainbow trout (Oncorhynchus mykiss) 96% Ethanol extract Iran [56] Rainbow trout (Oncorhynchus mykiss) 80% Ethanol extract Urmia, Iran [57] Nile tilapia (Oreochromis niloticus) Water extract Egypt [58] Nile tilapia (Oreochromis niloticus) Cereal alcohol extract Brazilian brown propolis [59] Nile tilapia (Oreochromis niloticus) fingerlings Ethanol extract Dakahlia province, Egypt [60] Carp (Cyprinus carpio) 70% Ethanol extract Poplar type [61] Preservative effect in food industry Beverages Unpasteurized fruit juices (apple, orange, white grape and mandarin) Ethanol extracts Turkey …”
Section: New Fields Of Propolis Applicationmentioning
confidence: 99%
“…Thus, the synergism between compounds in cashew (anacardic, cardol, and cardinal acids) and castor oils (ricinoleic acid) may improve their antimicrobial effect on microorganisms. The association of the compounds extracted from cashew and castor oils, similar effects were observed in comparison the sodium monensin (Cruz et al, 2014;Valero et al, 2015Valero et al, , 2014Valero et al, , 2011Zawadzki et al, 2021). However, the effects on carcass characteristics and meat quality remain unclear.…”
Section: Introductionmentioning
confidence: 65%